Understanding methane bioelectrosynthesis from carbon dioxide in a two-chamber microbial electrolysis cells (MECs) containing a carbon biocathode. (June 2015) - Zhen, Guangyin; Kobayashi, Takuro; Lu, Xueqin; Xu, Kaiqin
Highlights: A two-chamber microbial electrolysis cells was developed for the reduction of CO2 . Biocathode as electron donor was the vital driving force for electromethanogenesis. FISH analysis confirmed the mechanisms of direct electron transfer. Multiple pathways of electron transfer between cell-electrode were proposed. Abstract: To better understand the underlying mechanisms for methane bioelectrosynthesis, a two-chamber MECs containing a carbon biocathode was developed and studied. Methane production substantially increased with increasing cathode potential. Considerable methane yield was achieved at a poised potential of −0.9 V (vs. Ag/AgCl), reaching 2.30 ± 0.34 mL after 5 h of operation with a faradaic efficiency of 24.2 ± 4.7%. Confirmatory tests done at 0.9 V by switching the type of flushed substrates (CO2 /N2 ) or the electrical exposure modes (ON/OFF) demonstrated that cathode serving as an electron donor was the vital driving force for methanogenesis occurring at microbe–electrode surface. Fluorescence in situ hybridization reveled Methanobacteriaceae (particularly Methanobacterium ) was the predominant methanogens, supporting the mechanisms of direct electron transfer between cell-electrode. Additionally, the analysis of scanning electron microscope confirmed that the multiple pathways of electron transfer, including direct cathode-to-cell, interspecies exchange and semi-conductive conduits all together ensured the successful electromethanogenesis process.